Gust response of rigid and elastically mounted airfoils at a transitional Reynolds number - Barnes, Caleb J.; Visbal, Miguel R. (Aerospace science and technology, 2018)
This article explores the evolution of the unsteady flow structure for rigid and elastically mounted NACA0012 airfoils subject to a parallel vortical gust disturbance at a Reynolds number of Re=150,000 using implicit large-eddy simulation coupled with a structural dynamics model. A Taylor vortex is supplied upstream of the airfoil and shown to be successful at eliciting laminar separation flutter in the elastically mounted system under conditions which normally require an artificial disturbance. Much of the gust-induced moment responsible for flutter excitation is supplied by a two-stage flow transition process on the undersurface of the wing after the gust passes the airfoil. The gust response triggers transition of the separated lower-surface boundary layer into spanwise coherent vortices followed by a laminar separation bubble accompanied by a secondary emergence of flow transition. These events appear to be analogous in some ways to the processes that appear during fully developed flutter but occur over a shorter timescale.